A new species of Caecidotea (Crustacea: Isopoda: Asellidae) from a well in the western slope of Mexico, with occurrence records of C. alvarezi - García-Vázquez, Leonardo; Rodríguez-Almaraz, Gabino A.; Barragán-Ramírez, José Luis; Quiroz-Martínez, Benjamín (Zootaxa, 2024)
Caecidotea isabelae sp. nov., a new freshwater asellid isopod species from Jalisco, Mexico is described. During fieldwork in 2021, we discovered eight new populations of freshwater isopods belonging to the genus Caecidotea. One population corresponded to a new species, Caecidotea isabelae sp. nov., while the other seven populations were identified as Caecidotea alvarezi. These populations are reported from freshwater bodies on the western Trans-Mexican Volcanic Belt, expanding the distributional range of C. alvarezi through the state of Jalisco. The new species can be distinguished of their congeners mainly by the protopod of pleopod I triangular with 3 retinacula, exopod of pleopod III with 6 presutural setae, pleopod IV with 3 spines in the proximal external margin. The present study increases the number of known epigean asellid species in Mexico to 12, and the number of currently described Caecidotea species in North America to 102 with three subspecies.